Thromboelastogram and coagulation function index: relevance for female breast cancer - Peng, Qiongle; Zhu, Jinmei; Ren, Xiaoling (Frontiers in Oncology, 2024)
Introduction Screening and postoperative intervention of breast tumors are critical for the effective diagnosis and treatment of disease development, and reliable diagnostic/screening methods become a key link. Objective Thromboelastogram (TEG), routine platelet (PLT) count, and the coagulation function indicators in patients with different breast diseases were determined and analyzed to explore their predictive value in secondary bleeding disorders. Methods A total of 131 patients with breast diseases, admitted to Jiangsu University Affiliated Hospital from January 2019 to December 2022, were selected as the research subjects. The detection items were analyzed using the receiver operating curve (ROC) after grouping for secondary bleeding disorders of patients with breast cancer. Results The reaction (R) and the coagulation (K) times were lower in the malignant breast disease group, while the coagulation angle (α), maximum amplitude (MA), coagulation index (CI), fibrinogen (FIB), and D-dimer (D-D) were higher than those in the benign breast disease group. The t-tests proved that the MA and FIB values were statistically significant (p < 0.05) in the benign and malignant breast disease groups. The R and K in patients with breast diseases were positively correlated with the activated partial thromboplastin time (aPTT) and D-D, but were negatively correlated with PLT. The α angle was negatively correlated with aPTT and D-D, but was positively correlated with PLT. The MA for PLT function was positively correlated with FIB and PLT. CI was negatively correlated with aPTT, thrombin time (TT), and D-D, but was positively correlated with PLT. ROC curve analysis showed that the CI and α angle had a significant predictive value, whereas the correlation of the other indicators was relatively low. Conclusion Coagulation tests showed significant differences in patients with breast cancer, differing from those with benign breast diseases. TEG combined with conventional coagulation indicators is potentially valuable for the prediction of secondary bleeding disorders in patients with breast cancer.